Physical characterization of bacteriophages isolated against Salmonella Dublin - CHANDRA, MUDIT; THAKUR, SUNITA; NARANG, DEEPTI; SAXENA, H M (The Indian Journal of Animal Sciences, 2012)
In the present study a total of 5 phages were isolated against Salmonella Dublin using agar overlay technique from 25 samples of dairy effluent. These phages were purified, enriched and subjected to various physical (pH, temperature and sun light exposure) to evaluate their survival ability. On physical characterization of the phages it was found that the phages could survive varied pH conditions with reduction in its numbers from the initial concentration. Upon exposure to various temperature conditions it was observed that the phages can withstand a maximum 50°C and above this temperature it was deleterious for almost all the phages. Exposure to direct sunlight indicated that phages can withstand maximum continuous exposure up to 6 days and beyond that it was found to be deleterious for survival of the phage.